Stabilization treatment of remitted psychotic depression: the STOP‐PD study. (29th June 2018) - Bingham, K. S.; Meyers, B. S.; Mulsant, B. H.; Rothschild, A. J.; Whyte, E. M.; Banerjee, S.; Artis, A. S.; Alexopoulos, G. S.; Flint, A. J.; ,
Abstract : Objective: We conducted a 12‐week double‐blind study of stabilization pharmacotherapy in patients with remitted psychotic depression (PD). Methods: Seventy‐one persons aged 18 years or older who had achieved remission of PD when randomized to either olanzapine plus sertraline or olanzapine plus placebo were continued on the double‐blind treatment associated with remission. Symptoms of depression and psychosis, and weight, were measured once every 4 weeks. Cholesterol, triglycerides, and glucose were measured at stabilization phase baseline and Week 12/termination. Results: The effect of treatment did not significantly change with time for depression, weight, or metabolic measures in the stabilization phase. Eight of the 71 participants (11.3%; 95% CI: 5.8, 20.7) experienced a relapse of major depression, psychosis, or both. Treatment groups did not differ in the frequency of relapse. In the entire study group, the adjusted estimate for change in weight was an increase of 1.66 kg (95% CI: 0.83, 2.48) and the adjusted estimate for change in total cholesterol was a decrease of 14.8 mg/dL (95% CI: 3.5, 26.1) during the 12‐week stabilization phase; the remaining metabolic measures did not significantly change. Conclusion: Continuation of acute treatment was associated with stability of remission.